Titanium alloy cast ingot phase transformation point detection method

Through high-temperature solid solution and low-temperature aging processes, the problems of complex and poor accuracy of phase change point detection process of titanium alloy are solved, and efficient and accurate detection of phase change points of titanium alloy ingots are achieved.

CN119413549AActive Publication Date: 2025-02-11CHONGQING KINGSLEY AERONAUTICAL MATERIAL TECH CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411365998.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-11
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

In the prior art, the phase change point detection process of titanium alloy is complex, the detection accuracy is poor, and the internal tissue of the titanium alloy may deteriorate during the multi-fire forging process, increasing the detection cost and complexity.

Method used

Using high-temperature solution and low-temperature aging technology, samples were taken at the ingot riser, heated to Tβ+ (10-300)℃ and rapidly cooled, and then insulated at Tβ-(200-400)℃ and heated to Tβ-(30 ~60)℃, and finally the phase change point detection heat treatment is carried out, and the heat treatment temperature value is centered on Tβ and the equal difference value is distributed.

Benefits of technology

It improves the accuracy of phase change point detection of titanium alloy ingots, simplifies the detection process, reduces costs, avoids deterioration of internal tissue of titanium alloy, and achieves faster and more accurate detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119413549A_ABST
    Figure CN119413549A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of titanium alloy phase transformation point detection, and discloses a titanium alloy cast ingot phase transformation point detection method, which comprises the following steps: 1, carrying out high-temperature solid solution, sampling at a cast ingot riser to obtain a plurality of samples, heating all the samples to T beta + (10-300) DEG C, carrying out heat preservation, and carrying out rapid cooling; (2) low-temperature aging: preserving heat of all the samples cooled in the step (1) below T beta-(200-400), then heating to T beta-(30-60) DEG C, preserving heat and then cooling; step 3, phase change point detection heat treatment: all the samples cooled in the step 2 are divided into multiple groups, the multiple groups of samples are subjected to heat treatment at the same time, the number of heat treatment temperature values is equal to the number of the sample groups, and all the heat treatment temperature values are distributed in a gradient mode with Tbeta as the center and equal difference values; and 4, detecting a phase change point, and evaluating the phase change point according to the content of the high microstructure. The problems that in the prior art, the titanium alloy phase transformation point detection technology is complex, and the detection precision is poor are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium alloy phase transition point detection, and in particular to a titanium alloy ingot phase transition point detection method. Background Art

[0002] Titanium alloys have high specific strength, good ductility and good fracture toughness, and their market share in the aerospace field is increasing. High-end titanium alloy materials for aerospace use Titanium alloys are usually in (T β -50℃)~(T β +30℃) in a narrow range to obtain superior performance. In this range, especially when close to the phase transition point, the structure of titanium alloy will change significantly with the change of temperature, resulting in completely different product performance results. In particular, this kind of transformation is generally difficult to recover. In the actual production process, the phase transition point of the same grade of titanium alloy also varies greatly. Therefore, it is necessary to evaluate the phase transition point of each batch of titanium alloy materials for the production and application of titanium alloy.

[0003] Among the current testing methods, the conventional testing method is to use the α phase content to evaluate the phase transition point. Specifically, according to the phase transition process of titanium alloy, the closer to the phase transition point, the less α phase content. Therefore, in the testing process, it is only necessary to heat all the samples (the heating process is multiple samples, and the heating process is carried out at the empirical T β Set the temperature value equal to the number of samples and one-to-one correspondence nearby. The temperature value is based on the experience T β The phase transition point of the titanium alloy is determined by the following methods: (1) the phase transition point of the titanium alloy is determined by the following methods: (a) the phase transition point of the titanium alloy is determined by the following methods: (a) the phase transition point of the titanium alloy is determined by the following methods: (b) the phase transition point of the titanium alloy is determined by the following methods: (c) the phase transition point of the titanium alloy is determined by the following methods: (d) the phase transition point of the titanium alloy is determined by the following methods: (d) the phase transition point of the titanium alloy is determined by the following methods: (e) the phase transition point of the titanium alloy is determined by the following methods: (e) the phase transition point of the titanium alloy is determined by the following methods: (f) the phase transition point of the titanium alloy is determined by the following methods: (g ... Summary of the invention

[0004] The present invention aims to provide a method for detecting phase transition points of titanium alloy ingots, so as to solve the problems of complex process and poor detection accuracy in the prior art during the detection of phase transition points of titanium alloys.

[0005] The inventors discovered during the actual detection process that when the existing conventional technology is used to detect the phase transition point of the titanium alloy, when the ingot is heated to precipitate the α phase, due to the presence of the semi-coherent interface between the α phase and the β phase, only long and thin lamellar α phase can be precipitated. When approaching the phase transition point, the length of the α phase is very long but the thickness is very small. During the subsequent extreme water cooling, lamellar supercooled martensite will also precipitate in the titanium alloy. Its morphology is similar to that of the lamellar α phase and is difficult to distinguish, which interferes with the detection of the α phase. Therefore, it is difficult to evaluate the α phase content under an optical microscope, which ultimately results in poor detection accuracy of the phase transition point of the titanium alloy.

[0006] In order to solve the above problems, in the prior art, multiple forgings are usually performed before detection to interrupt the semi-coherent interface between the α phase and the β phase, and finally precipitate an equiaxed or short rod-shaped α phase in a balanced state, so that the morphology of the α phase is different from that of the supercooled martensite, which is convenient for the detection and viewing of the α phase, thereby improving the accuracy of the detection. The inventor found that although the α phase can be detected more clearly by using multiple forgings, in actual operation, the temperature value between the actual phase transition point of the ingot and the empirical phase transition point may have a large difference, and the internal structure of the titanium alloy may be deteriorated during the multiple forging process, thereby wasting a lot of time and material costs to remediate the forging of the blank to recover the loss, which increases the cost and complexity of the detection, and is not conducive to the rapid and accurate detection of the phase transition point of the titanium alloy ingot. Therefore, it is necessary to find a more convenient and accurate detection method to achieve better detection results.

[0007] To solve the above problems, the present invention adopts the following technical solution: a method for detecting phase transition points of titanium alloy ingots, comprising the following steps: Step 1: high temperature solid solution, sampling at the ingot riser to obtain multiple groups of samples, and heating all samples to T β + (10~300)℃, rapid cooling after heat preservation; Step 2: Low temperature aging: All samples cooled in step 1 are placed at T β - Keep warm below (200~400), then raise the temperature to T β - (30~60)℃, keep warm and then cool; Step 3: Phase transition point detection heat treatment: Divide all samples after cooling in step 2 into multiple groups, and heat treat multiple groups of samples at the same time. The number of heat treatment temperature values ​​is equal to the number of samples. All heat treatment temperature values ​​are expressed as T β A gradient distribution with equal differences at the center; Step 4: Phase transition point detection, evaluating the phase transition point based on high-magnification tissue content.

[0008] The principle of this scheme is: T in this application βAll of them are empirical phase transition points. In step one, the sample is rapidly cooled after solid solution in a single-phase region, so that the sample structure becomes a supersaturated solid solution. In the heating process after low-temperature aging in step two, due to the extremely large free energy difference, the driving force for the nucleation of the new phase is greatly increased, and the interface of the new phase is changed from a semi-coherent interface to an incoherent interface with higher interface energy. The α phase with an incoherent interface will spontaneously geometrize during the phase transition point heat treatment insulation process in the subsequent step three to form an equiaxed or short rod α phase, so that the α phase can be clearly identified during the phase transition point detection process in step four, and finally the phase transition point of the titanium alloy ingot can be detected conveniently and accurately.

[0009] The beneficial effects of this program are: 1. High detection accuracy: Compared with the prior art, which requires multiple forgings to obtain equiaxed or short-bar α phases for better observation and identification, not only is the process more complicated, but the internal structure of the titanium alloy will deteriorate during the multiple forging process, affecting the detection of the phase transition point of the titanium alloy ingot. In this application, through a specific high-temperature solid solution and low-temperature aging process, the sample is formed into an equiaxed or short-bar α phase, which effectively improves the display degree in the subsequent α phase detection process, which can not only effectively reduce the difficulty of detection, but also avoid the formation of lamellar α phase, and can clearly distinguish structures such as supercooled martensite, thereby improving the accuracy of phase transition point detection.

[0010] 2. Higher process feasibility: Compared with the detection method in the prior art, the detection process requires multiple forgings, which is not only complicated, but also causes the internal structure of the titanium alloy to deteriorate during the multiple forgings, affecting the detection of the phase transition point of the titanium alloy ingot. The detection process in this application does not require multiple forgings to form an α phase in an equiaxed or short rod shape that is easy to identify, which not only improves the detection accuracy, but also makes the process simpler and more feasible, and the detection cost is also lower.

[0011] 3. Ability to complete the test efficiently: In the present application, since the sample is processed by heat treatment process, it does not need to spend a lot of time on forging, etc., and multiple samples can be processed simultaneously in step one and step two, thereby completing the detection of the entire phase change point more efficiently.

[0012] 4. More accurately detect the phase transition point of titanium alloy: In this application, when setting the sample, the number of samples is multiple, and in step 3, multiple temperature values ​​are set that are equal to the number of samples and correspond one to one. All temperature values ​​are expressed in T β The central upper and lower gradient difference distribution can detect the phase change point of the corresponding furnace batch of titanium alloy more quickly and accurately.

[0013] Preferably, as an improvement, in step 2, at T β -The holding time at (200~400) temperature is 1~8h.

[0014] Preferably, as an improvement, in step 2, when the temperature is raised to T β -After (30~60)℃, the insulation time is 60~600 minutes.

[0015] Preferably, as an improvement, the cooling method in step 2 is air cooling.

[0016] Preferably, as an improvement, the insulation time in step 1 is 10 to 200 minutes.

[0017] Preferably, as an improvement, the cooling method in step one is water cooling.

[0018] Preferably, as an improvement, the difference between adjacent heat treatment temperature values ​​is 5°C.

[0019] Preferably, as an improvement, the heat treatment holding time in step three is 30 minutes, and the cooling method after the heat treatment holding is water cooling.

[0020] In this scheme, when sampling at the ingot riser position in step 1, the sampling position is located at the R / 2 position of the ingot riser.

[0021] Preferably, as an improvement, the number of groups of samples is 3 to 6, and the number of samples in each group is 5.

[0022] The beneficial effects of this program are: 1. In step 2, β The temperature is kept below 30-60℃ for a long time, and then gradually cooled to room temperature in air, so that the interface of the new phase changes from a semi-coherent interface to an incoherent interface with higher interface energy. The α phase will spontaneously geometrize and stably form an equiaxed or short rod α phase. The whole process is controllable and stable.

[0023] 2. Set the cooling method in step 1 to water cooling, so that the sample after high-temperature solution is rapidly cooled to form a supersaturated solid solution, which greatly increases the momentum of the α phase precipitation in step 2 and changes the morphology of the precipitated phase.

[0024] 3. The difference between adjacent heat treatment temperature values ​​in step three is 5°C. The phase transition point temperature range of different grades of titanium alloys is mostly in the range of 20-40°C. Therefore, the temperature difference between adjacent heat treatment temperature values ​​is set to 5°C. The phase transition point temperature of the titanium alloy can be detected more accurately and quickly. The number of samples is moderate and the temperature range can be conveniently and accurately controlled.

[0025] 4. The sampling position is located at the R / 2 position of the ingot riser. The organizational structure of the sample is closer to the actual structural morphology of the ingot, making the sampling more precise and the data obtained from the test more accurate.

[0026] 5. Set the sample to 3-6. Since the temperature difference between adjacent heat treatment temperature values ​​is 5°C, the entire sample can be tested in the range of 15-30°C, and T β is the empirical phase transition point, thus ensuring that the experiment is carried out at T β Conducting tests in the range of 15 to 30°C can accurately detect the actual phase change point of the ingot; in addition, the number of samples in each group of samples is set to 5, and setting multiple samples at the same temperature can effectively reduce the detection error and make the detection result more accurate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a high-magnification microstructure diagram of the sample in Example 1 of the present invention at a heat treatment temperature of 890° C. (the α phase content is 10%).

[0028] Figure 2 This is a high-magnification microstructure diagram of the sample in Example 1 of the present invention at a heat treatment temperature of 895° C. (the α phase content is 6%).

[0029] Figure 3 This is a high-magnification microstructure diagram of the sample in Example 1 of the present invention at a heat treatment temperature of 900° C. (α phase content <1%).

[0030] Figure 4 This is a high-magnification microstructure diagram of the sample in the comparative example after multiple forgings at a temperature of 890°C (the α phase content is 14%).

[0031] Figure 5 This is a high-magnification microstructure diagram of the sample in the comparative example after multiple forgings at a temperature of 895°C (the α phase content is 4%).

[0032] Figure 6 This is a high-magnification microstructure diagram of the sample in the comparative example after multiple forgings at a temperature of 900°C (the α phase content is <1%). DETAILED DESCRIPTION

[0033] The following is further described in detail through specific implementation methods: Embodiment 1 Embodiment 1: A method for detecting phase transition points of titanium alloy ingots, comprising the following steps: Step 1: high temperature solid solution, sampling at the ingot riser to obtain multiple groups of samples, the number of sample groups is preferably 3 to 6, and the number of samples in each group is 5, and the sampling position is located at the R / 2 position of the ingot riser, and all samples are heated to T at the same time after sampling β + (10-300)°C, keep warm and then cool rapidly. The keeping warm time is 10-200 minutes. The rapid cooling method is water cooling, and the water is cooled to room temperature.

[0034] Step 2: Low temperature aging: All samples cooled to room temperature in step 1 are placed at T β - (200 ~ 400) below the temperature, the temperature is kept for 1 ~ 8h, and then the sample is heated to T β - (30~60)℃, keep warm and then cool, the keeping time is 60~600 minutes, the cooling method is air cooling.

[0035] Step 3: Phase transition point detection heat treatment: Divide all samples after cooling in step 2 into multiple groups, and heat treat multiple groups of samples at the same time. The number of heat treatment temperature values ​​is equal to the number of sample groups. All heat treatment temperature values ​​are expressed as T β The temperature difference between adjacent heat treatment temperature values ​​is 5°C. For example, if there are five samples, the number of heat treatment temperature values ​​is also five, and the five temperature values ​​are T β -10℃、T β -5℃、T β , T β +5℃、T β +10℃, so that different samples are treated at different heat treatment temperature values, where the heat treatment holding time is 30 minutes, and after heat treatment, the samples are water-cooled to room temperature.

[0036] Step 4: Phase transition point detection, evaluating the phase transition point based on high-magnification tissue content.

[0037] Specifically, in this embodiment, a typical TC17 titanium alloy is used as an example. The nominal composition of the TC17 titanium alloy is Ti-5Al-4Mo-4Cr-2Sn-2Zr, and the empirical average β transformation temperature is 895°C (i.e., T β The value is 895℃), the experimental steps are as follows: Step 1: high temperature solid solution, sampling at the ingot riser to obtain three groups of samples, each group of samples has 5 samples, and the sampling position is located at the R / 2 position of the ingot riser, the sampling size is 10×10mm, and all samples are heated to 930℃ (i.e. T β +35℃), keep warm for 30 minutes and then cool with water.

[0038] Step 2: Low temperature aging: All samples cooled to room temperature in step 1 are aging at 600°C (T β -295℃) for 120 minutes, and then the sample was heated to 850℃ (T β -45℃), keep warm for 120 minutes and then air cool.

[0039] Step 3: Phase transition point detection heat treatment: the three groups of samples after cooling in step 2 are placed at three temperatures of 890°C, 895°C and 900°C for heat treatment for 30 minutes, and then water-cooled.

[0040] Step 4: Phase transition point detection, check the high-magnification tissue content, and then evaluate the phase transition point based on the high-magnification tissue content. The test results are as follows: Figure 1-Figure 3 shown.

[0041] Comparative Example: Three samples were taken from the ingot in the manner of step 1, and the three samples were tested according to the multi-fire forging method in the prior art. The temperatures of the multi-fire forging were 890°C, 895°C, and 900°C, respectively, corresponding to the heat treatment temperature values ​​of the three samples in this embodiment. The test results are as follows: Figure 4-Figure 6 shown.

[0042] according to Figure 1-Figure 6 It can be seen from the comparison that when the sample is treated by the process method of this embodiment, when the phase transition point is detected, the α phase obtained by the treatment of this embodiment is in the form of equiaxed or short rods, which can be clearly and conveniently identified when the high-magnification tissue content is detected. Figure 4-6 The microstructures obtained by multiple forgings are basically the same. Based on the α phase content of less than 3% as the basis for judging the phase transformation point, the final results of the two groups of tests are both 895~900℃, indicating that the phase transformation point determined by this technology is highly accurate and has high reliability in guiding subsequent forging processes.

[0043] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for detecting phase transition point of a titanium alloy ingot, comprising the following steps: Step 1: high temperature solid solution, sampling at the ingot riser to obtain multiple groups of samples, and heating all samples to T β + (10~300)℃, rapid cooling after heat preservation; Step 2: Low temperature aging: All samples cooled in step 1 are placed at T β - Keep warm below (200~400), then raise the temperature to T β - (30~60)℃, keep warm and then cool; Step 3: Phase transition point detection heat treatment: Divide all samples after cooling in step 2 into multiple groups, and heat treat multiple groups of samples at the same time. The number of heat treatment temperature values ​​is equal to the number of samples. All heat treatment temperature values ​​are expressed as T β Gradient distribution with a fixed temperature difference at the center; Step 4: Phase transition point detection, evaluating the phase transition point based on high-magnification tissue content.

2. A titanium alloy ingot phase transition point detection method according to claim 1, characterized in that: In step 2, β -The holding time at (200~400) temperature is 1~8h.

3. The method for detecting phase transition point of a titanium alloy ingot according to claim 1, characterized in that: In step 2, the temperature is raised to T β -After (30~60)℃, the insulation time is 60~600 minutes.

4. The method for detecting phase transition point of a titanium alloy ingot according to claim 1, characterized in that: The cooling method in step 2 is air cooling.

5. The method for detecting phase transition point of titanium alloy ingot according to claim 1, characterized in that: The insulation time in step 1 is 10 to 200 minutes.

6. The method for detecting phase transition point of a titanium alloy ingot according to claim 1, characterized in that: The cooling method in step 1 is water cooling.

7. The method for detecting phase transition point of titanium alloy ingot according to claim 1, characterized in that: The difference between adjacent heat treatment temperature values ​​is 5°C.

8. The method for detecting phase transition points of titanium alloy ingots according to claim 1, characterized in that: The heat treatment holding time in step 3 is 30 minutes, and the cooling method after the heat treatment holding is water cooling.

9. The method for detecting phase transition point of titanium alloy ingot according to claim 1, characterized in that: When sampling at the ingot riser position in step 1, the sampling position is located at the R / 2 position of the ingot riser.

10. A method for detecting phase transition points of titanium alloy ingots according to any one of claims 1 to 9, characterized in that: The number of groups of the samples is 3 to 6, and the number of samples in each group is 5.

Citation Information

Patent Citations

  • Manufacturing method for titanium alloy large-specification ring piece with basket-weave microstructure

    CN111318581A

  • Method for measuring phase transformation point temperature of beta single-phase region titanium alloy through recrystallization

    CN112051294A

  • Heat treatment method for improving strength and plasticity matching of Ti-575 double-phase titanium alloy through multi-scale heterogeneous alpha-phase precipitation

    CN116676547A

  • Preparation method for additive manufacturing titanium alloy

    CN117620205A

  • Processing technology of high-strength and high-plasticity titanium alloy

    CN118291896A